Heterogeneous Condition of Asthmatic Children Patients: A Narrative Review - Cristiano Caruso; Stefania Colantuono; Stefania Arasi; Alberto Nicoletti; Antonio Gasbarrini; Angelo Coppola; Loreta Di Michele (MDPI AG, 2022)
Currently, asthma represents the most common chronic disorder in children, showing an increasingly consistent burden worldwide. Childhood asthma, similar to what happens in adults, is a diversified disease with a great variability of phenotypes, according to genetic predisposition of patients, age, severity of symptoms, grading of risk, and comorbidities, and cannot be considered a singular well-defined disorder, but rather a uniquely assorted disorder with variable presentations throughout childhood. Despite several developments occurring in recent years in pediatric asthma, above all, in the management of the disease, some essential areas, such as the improvement of pediatric asthma outcomes, remain a hot topic. Most treatments of the type 2 (T2) target phenotype of asthma, in which IL-4, IL-5, and IL-13 modulate the central signals of inflammatory reactions. Although, there may be an unresolved need to identify new biomarkers used as predictors to improve patient stratification using disease systems and to aid in the selection of treatments. Moreover, we are globally facing many dramatic challenges, including climate change and the SARS-CoV2 pandemic, which have a considerable impact on children and adolescent asthma. Preventive strategies, including allergen immunotherapy and microbiome evaluation, and targeted therapeutic strategies are strongly needed in this population. Finally, the impact of asthma on sleep disorders has been reviewed.